Evolution of fluvial system in Siwalik Group of Chatara-Barahakshetra area, east Nepal Himalaya (Journal of Nepal Geological Society, 2004)
Four facies associations (i.e., FA1 to FA4) are recognised in the Siwalik molasse of the Chatara-Barahakshetra area in east Nepal. They are classified based on the proportion of sandstone and mudstone, individual bed thickness, and bedform types. The facies associations are intimately related to the lithostratigraphic units of the Siwalik Group. The lower and upper members of the Lower Siwaliks (FA1- and FA2-facies associations, respectively) are inferred to be the products of fine-grained meandering and flood flow-dominated meandering fluvial systems, respectively. Similarly, the lower and middle members or the Middle Siwaliks (FA3- and FA4-facies associations, respectively) are interpreted as the deposits of sandy meandering and sandy braided fluvial systems, respectively.